Oxynoemacheilus shehabi, a new nemacheilid loach from the upper Orontes in southern Syria (Teleostei: Nemacheilidae) - Freyhof, Jörg; Geiger, Matthias F. (Zootaxa, 2021)
Oxynoemacheilus shehabi, new species, is described from the upper Orontes in southern Syria. It is distinguished from other Oxynoemacheilus species in the Levant by possession of a complete lateral line, a deeply emarginate caudal fin, a narrow caudal peduncle, a suborbital groove in male individuals, a well-developed pelvic axillary lobe, and 5–7 dark-brown bars on the flank. Molecular data suggest that the new species is characterised by a minimum K2P distance of 3.8% to O. “seyhanicola” in the COI mtDNA barcode region.